Reinvestigation of carbohydrate specificity of EB-A2 monoclonal antibody used in the immune detection of Aspergillus fumigatus galactomannan - Krylov, Vadim B. (Heliyon, 2019)
Great progresses have been made in the recent years in the detection of circulating galactofuranose-bearing molecules for the diagnosis of aspergillosis. However, the test used in the clinical practice is hampered by the occurrence of false positives. A glycoarray with dozens of oligosaccharides structurally related to the Aspergillus fumigatus galactomannan has allowed us to reinvestigate the carbohydrate specificity of the EB-A2 monoclonal antibody used in the Platelia(TM) Aspergillus sandwich immune assay. We have now demonstrated that the mAb can recognize shorter oligosaccharides than the previously reported tetrasaccharide Galf-β-(1→5)-Galf-β-(1→5)-Galf-β-(1→5)-Galf-β and oligosaccharides which contains alternating β-(1→5)/β-(1→6)-linkages. This result could explain the occurrence of false-positive signals due to the presence of the abovementioned epitopes not only in A. fumigatus galactomannan but also in other bacteria and fungi.